ARGUMEN EKSISTENSI TUHAN DALAM METAFISIKA IBN RUSYD DAN ST. THOMAS AQUINAS - Wardani (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2015)
To establish an argumentation for the existence of God is properly the most crucial as well as complicated effort in the life of religion and faith of human being. There are various approaches and methods have been applicated to reach it by theologians, thinkers, and scientists, including philosophers with their demonstrative-philosophical method. Some arguments which were initiated by Aristotle are ones of the most popular and have been adopted and improved as well by many thinkers and philosophers after him, some arguments which proposed by Ibn Rusyd and St. Thomas Aquinas with some modifications and improvisations are the best examples of it. In the case of elaboration and analysis toward those arguments for the existence of God, this article attempts to compare between metaphysical thought of Ibn Rushd (well-known in the West as Averroës) and St. Thomas Aquinas. There is no doubt that both are Aristotelian in their philosophy. Therefore, to seek the similarities and differences, and to analyze the influence of Aristotle on their modes of thought, especially in argumentation for the existence of God, are an urgent point in the way to find more stronger and relevant arguments.